Indian Rights for Indian Babies: Canada’s “Unstated Paternity” Policy - Gehl, Lynn (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Relying on an Indigenous methodology and the methods of a literature analysis, personal experience, and critical introspection this article addresses Aboriginal Affairs and Northern Development Canada’s 1985 unstated paternity policy in regard to the Indian status provisions of the Indian Act. Through Canada’s unstated paternity policy, with its inherent assumption where the Registrar of Aboriginal Affairs interprets all applicants’ birth certificates that lack a father’s signature as being a non-Indian man, many Indigenous women and their children continue to be denied the right to live free from sex discrimination. Disturbingly, this unstated paternity policy applies in situations of sexual violence such as incest, rape, gang rape, sexual slavery, and prostitution where young mothers of Indigenous Nations are particularly vulnerable. Thus, despite Canada’s Charter of Rights and Freedoms and the two remedial legislations that took place in 1985 and 2011 purportedly to eliminate the sex discrimination in the Indian Act, in Canada’s continued need to eliminate treaty responsibilities to Indigenous nations, the nation state is directly targeting Indigenous babies. While policy remedies are discussed, the author also argues that despite the decades of advocacy and litigation work by Indigenous women, Canada has manipulated the remedial legislative process as an opportunity to create new forms of sex discrimination rather than eliminate it. In this way Canada acts in bad faith and in a way that is counter to the Charter.